Over-expression of histone H3K4 demethylase gene JMJ15 enhances salt tolerance in Arabidopsis - Shen, Yuan; Conde e Silva, Natalia; Audonnet, Laure; Servet, Caroline; Wei, Wei; Zhou, Dao-Xiu (Frontiers in Plant Science, 2014)
Histone H3 lysine 4 trimethylation (H3K4me3) has been shown to be involved in stress-responsive gene expression and gene priming in plants. However, the role of H3K4me3 resetting in the processes is not clear. In this work we studied the expression and function of Arabidopsis H3K4 demethylase gene JMJ15. We show that the expression of JMJ15 was relatively low and was limited to a number of tissues during vegetative growth but was higher in young floral organs. Over-expression of the gene in gain-of-function mutants reduced the plant height with accumulation of lignin in stems, while the loss-of-function mutation did not produce any visible phenotype. The gain-of-function mutants showed enhanced salt tolerance, whereas the loss-of-function mutant was more sensitive to salt compared to the wild type. Transcriptomic analysis revealed that over-expression of JMJ15 down-regulated many genes which are preferentially marked by H3K4me3 and H3K4me2. Many of the down-regulated genes encode transcription regulators involved in stress responses. The data suggest that increased JMJ15 levels may regulate the gene expression program that enhances stress tolerance.